Waqf Management Strategy In Accelerating Digitalisation And Islamic Financial Literacy For UMKM Under Micro Waqf Bank's Guidance - Fithri Dzikrayah; Fahmi Hasan Nugroho; Mia Lasmi Wardiyah; Izzul Haq Firman Maulana; Rika Afrianti Putri (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2024)
This study aims to analyze waqf strategy management in an effort to accelerate digitalization and Islamic financial literacy for micro waqf bank-assisted MSMEs. This research is a descriptive study using a qualitative approach. Data collection techniques are observation, interview, and documentary study. Data collection was carried out using interviews and observations to LKMS-BWM Barokah Pondok Pesantren Al-Masthuriyah and assisted MSMEs as BWM customers and literature studies. This research was analyzed using the SWOT method. The results showed that the development strategy for accelerating digitalization and Islamic financial literacy for MSMEs assisted by the Micro Waqf Bank in quadrant 1 is an aggressive strategy or S-O (Strengh-Opportunity) strategy, meaning that BWM can use existing strengths to take advantage of opportunities. This strategy is positive, meaning that basically, the development of BWM is good and can be developed further by utilizing existing opportunities. BWM can optimize programs registered and supervised by the Financial Services Authority, government-supported programs, implementation in accordance with Sharia principles/SOPs that have been established, cooperation with various parties, implementation in accordance with Sharia principles/SOPs that have been established, and catalysts for bankable MSME customers. I am also able to maximize current financing opportunities with joint responsibility for the use of developing technology with the BWM mobile application. Business coaching and mentoring are always presented to customers.